Interpretasi Makna Hadis Bepergian di Malam Hari - Bagus Wira Yoga . S; Uswatun Hasanah; Hedhri Nadhiran (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Traveling out of the house at night is where the conditions are very calm and quiet so it makes a person feel comfortable. However, in this day and age, there are many crimes occurring anywhere and at any time, especially at night, so that many crime phenomena such as robbery, theft, kidnapping, sexual harassment, and others have been spread in the media recently. Traveling at night has positive and negative impacts, according to the hadith narrated by Imam Abu Daud, Imam Al-Bukhari. This research aims to find out the meaning of the hadith of traveling at night using qualitative library research methods. The results of this research study are that interpreting the hadith of traveling at night has relevance to crimes that occur today. The conclusion is that for someone who wants to leave the house, they should look at the situation when they want to leave the door of the house, because crime can always happen at any time and anywhere.